Embodied immersive experiences: A path to facilitating connection to non-human nature - Scherini, Rebecca (Curtin University, 2022)
By using ‘sensory autoethnography’ this thesis demonstrates how planners can overturn binary ways of thinking in which humans’ concerns are placed above those of non-humans, promoting new ways of planning in the Anthropocene. Planners can foster more connected relationships to non-human nature by developing a sense of self as a body-subject, engaging in and facilitating ‘embodied immersive experiences’ in ‘natural spaces’, reimagining planning practice and feeding this back into education and training, and becoming embodied practitioners.